2009
DOI: 10.1590/s0103-90162009000400008
|View full text |Cite
|
Sign up to set email alerts
|

Minas-type fresh cheese developed from buffalo milk with addition of L. acidophilus

Abstract: Effective incorporation of a probiotic into foods requires the culture to remain viable all along processing and storage, without adverse alterations to sensory characteristics. The objective of this work was developing Minas-type fresh cheese with probiotic properties from buffalo milk. Four batches of Minas-type fresh cheese were prepared using buffalo milk: batch T1 in which neither culture nor lactic acid added; batch T3 in which only lactic acid added; batches T2 and T4 , both added of Lactobacillus acido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
3
5
1
Order By: Relevance
“…A drop in pH values was uniform in all whey cheese matrices, decreasing around 1.0 unit, regardless of initial probiotic cell concentration or formulation. Similar findings were found in probiotic “Minas Frescal” cheese (semi-soft) supplemented with L. acidophilus [ 36 ]. However, absolute pH values exhibited significant differences between matrices, with WCPSTC being the most distinct from the rest.…”
Section: Resultssupporting
confidence: 84%
“…A drop in pH values was uniform in all whey cheese matrices, decreasing around 1.0 unit, regardless of initial probiotic cell concentration or formulation. Similar findings were found in probiotic “Minas Frescal” cheese (semi-soft) supplemented with L. acidophilus [ 36 ]. However, absolute pH values exhibited significant differences between matrices, with WCPSTC being the most distinct from the rest.…”
Section: Resultssupporting
confidence: 84%
“…Buriti et al (2005) also found good acceptance of Minas fresh cheese with added L. acidophilus. In other studies, with fresh or ripened cheeses with added L. acidophilus, fresh buffalo Minas cheese (Marcatti et al, 2009) and Turkish white cheese (Kasimo lu et al, 2004), no negative effect on acceptance of the samples was observed. The addition of probiotic cultures to a food should not result in lower acceptance of the food compared with a similar conventional product (Cruz et al, 2010a), as shown in the development of various probiotic cheeses, such as Iranian white cheese produced by ultrafiltration (Zomorodi et al, 2011), Turkish Beyaz cheese (Kılıç et al, 2009), and Pategras cheese (Perotti et al, 2009).…”
Section: Consumer Testmentioning
confidence: 83%
“…It is thus indispensable that the development of prebiotic, probiotic, and/or synbiotic products be accompanied by specific sensory analyses to allow for the acquisition of the best conditions and of real knowledge in the search for products well accepted on the consumer market, be they of animal or vegetable origin (Figure 2). Some studies have reported the possibility of obtaining similar, or even better, performance with probiotic or prebiotic products as compared to conventional products: this was shown for low‐fat salami sausage with added inulin (Mendonza and others 2001), functional yogurt supplemented with L. reuteri RC‐14 and L. rhamnosus GR‐1 (Hekmat and Reid 2006), coconut pudding with added L. paracasei and B. lactis (Correa and others 2008), chocolate mousse with added inulin and L paracasei (Aragon‐Alegro and others 2007), fresh Minas‐type cheese made with cow milk (Souza and others 2007) and with buffalo milk (Marcatti and others 2009) supplemented with L. acidophilus , grape juice with inulin, and L. acidophilus (Santos and others 2008), chocolate and lemon‐flavored muffins supplemented with tagatose (Armstrong and others 2009), banana yogurt supplemented with L. acidophilus and Bifidobacterium spp. (Bakirci and Kavaz 2008), milk fermented with B. animalis and L. acidophilus La‐5, and supplemented with inulin (Oliveira and Jurkiewicz 2009), and corn‐snacks manufactured with fructans‐based fat replacer enriched with inulin and oligofructose (Capriles and others 2009).…”
Section: Probiotic Prebiotic and Synbiotic Foodsmentioning
confidence: 99%